2022
DOI: 10.14569/ijacsa.2022.0130153
|View full text |Cite
|
Sign up to set email alerts
|

A Conceptual User Experience Evaluation Model on Online Systems

Abstract: An online system has become a priority for organisations or companies in many countries, as it allows many processes to be conducted via online platforms, which contributes to profit gain. There are different types of user experience (UX) evaluation models that have been proposed to guide the measurement and development process. However, most of these models only have dimensions, and there is no guidance for UX measurement on online systems. The lack of evaluation models for online system measurement requires … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
1
0
Order By: Relevance
“…The UX evaluation criteria were developed to evaluate comprehensively the UX of e-commerce websites in terms of measuring the utilitarian quality and hedonic quality of any such site due to the lack of user experience (UX) criteria to evaluate specifically the user experience of e-commerce websites, with specific metrics (Bonastre and Granollers, 2014;Sudiana et al, 2021;Bascur et al, 2021;Yusof et al, 2022). It is worth mentioning that some studies were found in the literature that suggested heuristics or key factors regarding user experience or the usability evaluation of e-commerce websites (Bonastre and Granollers, 2014;Sudiana et al, 2021;Bascur et al, 2021;Hasan and Morris, 2017).…”
Section: Development Of User Experience (Ux) Criteriamentioning
confidence: 99%
See 2 more Smart Citations
“…The UX evaluation criteria were developed to evaluate comprehensively the UX of e-commerce websites in terms of measuring the utilitarian quality and hedonic quality of any such site due to the lack of user experience (UX) criteria to evaluate specifically the user experience of e-commerce websites, with specific metrics (Bonastre and Granollers, 2014;Sudiana et al, 2021;Bascur et al, 2021;Yusof et al, 2022). It is worth mentioning that some studies were found in the literature that suggested heuristics or key factors regarding user experience or the usability evaluation of e-commerce websites (Bonastre and Granollers, 2014;Sudiana et al, 2021;Bascur et al, 2021;Hasan and Morris, 2017).…”
Section: Development Of User Experience (Ux) Criteriamentioning
confidence: 99%
“…However, this model is general and does not include specific metrics to evaluate the utilitarian and hedonic quality of e-commerce websites. Similarly, Yusof et al (2022) suggested a conceptual user experience evaluation model for online systems. However, metrics to measure use experience were not identified.…”
Section: Development Of User Experience (Ux) Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…While Biduski et al [14] define UX as all aspects that are related to end-user interaction with a product or service. Thus, UX refers to the process of reviewing one's experience before, during and after using a product, system, or service [13] and is related to positive or negative emotions users feel in a specific context [15].…”
Section: Introductionmentioning
confidence: 99%